A D8-compatible high-efficient channel head recognition method. (March 2020) - Li, Jiaye; Li, Tiejian; Zhang, Li; Sivakumar, Bellie; Fu, Xudong; Huang, Yuefei; Bai, Rui
Abstract: As the resolution of DEMs is becoming higher, both the efficiency and accuracy of channel head recognition are important for drainage network extraction. In this paper, a D8-compatible high-efficient channel head recognition method is proposed. For each potential channel, this method first calculates a geomorphologic parameter series along the flow path, and then determines the channel head by detecting the change point in the series. Instead of directly using one threshold value for a whole region that is still commonly used in D8-based methods, the proposed method recognizes channel heads by their local geomorphology one by one. The proposed method is applied with high resolution DEMs for different terrains, and the identified channel heads and extracted drainage networks show good agreement with observations. In comparison with a popular software with state-of-the-art channel head recognition method, the proposed one shows similar accuracy but much higher computational efficiency. Highlights: We developed a D8-compatible high-efficient method to identify channel heads. Channel head is detected as the geomorphologic change point along each flow path. Flow path screening and dynamic window method facilitate the change point detection. Application in a D8-based software showed accurate results and high efficiency.